An Investigation of Variation Orders in Building Projects at the University for Development Studies, Tamale - Baba-Duah, Jawhari (Ghana Journal of Higher Education Management, 2023)
This study provides an overview of the types, causes, effects and management of variations in building projects at the University for Development Studies (UDS). The effects of variations, including but not limited to cost and time overruns, were investigated at UDS in order to implement appropriate management and control practices on their occurrences. A structured questionnaire was administered to 46 building and construction consultants in UDS. Of this number, which was determined using the Kish (1965) formula for sample size determination, valid data retrieved and analysed represented a response rate of 93 per cent (43). The results of the study revealed that variations constituted not less than 75% of instructions issued at the site and were mainly initiated by the consultant. The occurrence of variations on projects impacted regard to cost and time overruns but was however seen to contribute to the overall improvement of quality in the projects. Recommendations for managing variation orders include effective coordination among consultants, detailed specifications, detailed site analysis and setting up expenditure limits for variations in building contracts at UDS